Low dose propofol vs. lidocaine for relief of resistant post-extubation laryngospasm in the obstetric patient - Mokhtar,Ali M. (2018)
Abstract Background Post-extubation laryngospasm is a dangerous complication that should be managed promptly. Standard measures were described for its management. We aimed to compare the efficacy of propofol (0.5 mg.kg-1) vs. lidocaine (1.5 mg.kg-1) for treatment of resistant post-extubation laryngospasm in the obstetric patients, after failure of the standard measures. Method This study was conducted over 2 years on all obstetric patients scheduled for cesarean delivery. Post-extubation laryngospasm was initially managed with a standard protocol (removal of offending stimulus, jaw thrust, positive pressure ventilation with 100% oxygen). When this protocol failed, the tested drug was the second line (lidocaine in the first year and propofol in the second year). Lastly, succinylcholine was used when the tested drug failed. Results In lidocaine group, 5% of parturients developed post-extubation laryngospasm, 31.9% of them were successfully treated via standard protocol, and 68.1% required lidocaine treatment. Among these, 65.6% of patients treated with lidocaine responded successfully and 34.4% required succinylcholine to relieve laryngospasm. In propofol group, 4.7% of parturients developed post-extubation laryngospasm, 30.1% of them were successfully treated via standard protocol, and 69.9% required propofol treatment. Among these, 82.8% of patients treated with propofol responded successfully and 17.2% required succinylcholine to relieve laryngospasm. Conclusion Small dose of propofol (0.5 mg.kg-1) is marginally more effective than lidocaine (1.5 mg.kg-1) for the treatment of resistant post-extubation laryngospasm in obstetric patients, after failure of standard measures and before the use of muscle relaxants.